2005
DOI: 10.1111/j.0022-202x.2005.23836.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular pH Controls NHE1 Expression in Epidermis and Keratinocytes: Implications for Barrier Repair

Abstract: We have previously shown that the Na+/H+ antiporter (NHE1) is an essential endogenous pathway responsible for stratum corneum (SC) acidification. Since the epidermis must re-establish its epidermal barrier after acute barrier perturbations, we asked whether the NHE1 was, in turn, regulated by changes in barrier status. We found that in vivo epidermal NHE1 expression was upregulated within hours of barrier disruption. We next asked whether NHE1 was regulated by barrier status per se, or by the SC alkalinization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…This information is supported by our results of a likewise continuous production of the antiporter NHE-1 that regulates the pH conditions for barrier formation. NHE-1 controls the acidification of extracellular microdomains that are essential for activation of pH-sensitive enzymes to guarantee, most essentially, undisturbed repair of the epidermal permeability barrier (Behne et al 2002;Hachem et al 2005). We could also show, for example, that NHE-1 not only accumulates in the stratum granulosum, as demonstrated for laboratory rats (e.g.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This information is supported by our results of a likewise continuous production of the antiporter NHE-1 that regulates the pH conditions for barrier formation. NHE-1 controls the acidification of extracellular microdomains that are essential for activation of pH-sensitive enzymes to guarantee, most essentially, undisturbed repair of the epidermal permeability barrier (Behne et al 2002;Hachem et al 2005). We could also show, for example, that NHE-1 not only accumulates in the stratum granulosum, as demonstrated for laboratory rats (e.g.…”
Section: Discussionsupporting
confidence: 56%
“…In the keratinocytes, NHE-1 is essential for acidifying the lipid microdomains (lipid rafts; Wenneckes et al 2009) and very important for barrier repair or recovery (e.g. Behne et al 2002;Hachem et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In response to acute alkalinization as in barrier disruption, NHE1 upregulation allows a quick response to restore epidermal permeability barrier homeostasis. 32,33 Therefore, alkalization of extracellular space might explain the compensatory up-regulation of NHE1 protein levels that we observed in SC of FAK K5 KO mice. Yet, even higher total NHE1 protein levels did not suffice to bring pH down to normal acidic values, because NHE1 failed to translocate to the plasma membrane in terminally differentiated FAK Ϫ/Ϫ keratinocytes.…”
Section: Discussionmentioning
confidence: 80%
“…NHE1 must be localized at the plasma membrane of terminally differentiated keratinocytes to regulate extracellular pH. 33,36 Immunolocalization studies confirmed that very little of NHE1 translocated from the cytosol to the plasma membrane in the upper SG of FAK K5 KO mice ( Figure 6B levels of terminal differentiation, assessed as expression levels of early (involucrin) and late (loricrin) differentiation markers ( Figure 7B). As in our in vivo studies presented above, NHE1 translocation was defective in differentiated keratinocytes lacking functional FAK, whereas NHE1 production was not significantly affected.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation